Effect of soy protein isolate on the functional, pasting, and sensory acceptability of cassava starch-based custard - Akinwale, T.E.; Shittu, T.A.; Adebowale, A.A.; Adewuyi, S.; Abass, A. (Wiley, 2017)
Fortification of custard powder (CP) with protein from cheap sources such as soybean could potentially improve its nutritive value but may alter its functional and sensory properties. This study was therefore conducted to determine the effect of soy protein isolate (SPI) inclusion (0%–20%) on some functional and sensory properties of cassava starch-based CP. Functional, pasting, and sensory acceptability were determined using standard methods. Increase in soy protein isolate significantly (p < .05) decreased dispersibility, packed bulk density, swelling power, peak, trough, breakdown, final, and setback viscosities, but increased least gelation concentration, water absorption capacity, and solubility index. This study further showed that despite increasing addition of SPI up to 20%, sensory acceptability of the cassava starch-based CP formulations did not differ significantly, and most of them had very similar acceptability when compared to that of corn starch-based CP.